Political Will Of The Mandate Of The Covenant In Umayyad Period - Mahdi Al Nasiri, Imad Tali (Opción, 2019)
The commandments are immortal living documents in which the forerunner provides the summary of his experiences, and charts for him the proper paths he takes in his life and the issues and problems he faces. It is an art that reflects another aspect of the eloquence of rulers and men of politics in the field of prose, as well as the contents, experiences, and outlooks that make an impor- tant contribution to crystallizing the strings and milestones of political thought during this important era in the history of Islam. The commandment is a way to advise their guardians and their successors, in which they draw the political approach and it appears that the impact of the mandate of the covenant on the end of the Umayyad rule began when he took over the reigns of the unworthy of this great responsibility, which is the caliphate, and we reached this study to some important results, the most prominent of which is the divisions within the Umayyad effect Great in the deterioration of relations between them and the increase in the gap and problems between the brother and the uncle and the nephew, and the problem arose from the beginning when Muawiyah an- nounced the mandate of the covenant to his son Yazid, but it was magnified when he accumulated and sounded the alarm of the fall of the Umayyad state.